2021
DOI: 10.1159/000516213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Finerenone Combined with Empagliflozin in a Model of Hypertension-Induced End-Organ Damage

Abstract: <b><i>Introduction:</i></b> The nonsteroidal mineralocorticoid receptor (MR) antagonist finerenone and sodium-glucose cotransporter-2 (SGLT2) inhibitors have demonstrated clinical benefits in CKD patients with type 2 diabetes. Clinical data analyzing the potential value of a combination therapy are currently limited. We therefore investigated cardiorenal protection of respective mono- and combination therapy in a preclinical model of hypertension-induced end-organ damage. <b><i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 32 publications
4
77
0
3
Order By: Relevance
“…Finerenone is a nonsteroidal and selective mineralocorticoid receptor antagonist which belongs to RAAS inhibitors. Moreover, the combination therapy of empagliflozin and finerenone showed greater cardiovascular benefits than the empagliflozin or finerenone monotherapy in rats with preclinical hypertension-induced cardiorenal disease ( Kolkhof et al, 2021 ). Therefore, a gliflozin combined with finerenone is promising to yield greater cardiorenal benefits in patients with diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Finerenone is a nonsteroidal and selective mineralocorticoid receptor antagonist which belongs to RAAS inhibitors. Moreover, the combination therapy of empagliflozin and finerenone showed greater cardiovascular benefits than the empagliflozin or finerenone monotherapy in rats with preclinical hypertension-induced cardiorenal disease ( Kolkhof et al, 2021 ). Therefore, a gliflozin combined with finerenone is promising to yield greater cardiorenal benefits in patients with diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…13 A preclinical rat study of cardio-renal disease demonstrated that combination therapy with empagliflozin and finerenone resulted in a synergistic effect on albuminuria lowering and improved survival compared with either therapy alone. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, they found that finerenone exerted cardiorenoprotective effects independent of its blood pressure reduction ( Kolkhof et al, 2014 ). Combination therapy of empagliflozin and finerenone has also been shown to prevent proteinuria as well as cardiac and kidney fibrosis in hypertensive rats ( Kolkhof et al, 2021 ).…”
Section: Non-steroidal Mineralocorticoid Receptor Antagonistmentioning
confidence: 99%